Muscarinic receptor M3 activation promotes fibrocytes contraction - Henrot, Pauline; Eyraud, Edmée; Maurat, Elise; Point, Sophie; Cardouat, Guillaume; Quignard, Jean-François; Esteves, Pauline; Trian, Thomas; Girodet, Pierre-Olivier; Marthan, Roger; Zysman, Maéva; Berger, Patrick; et al. (Frontiers in Pharmacology, 2022)
Fibrocytes are monocyte-derived cells able to differentiate into myofibroblasts-like cells. We have previously shown that they are increased in the bronchi of Chronic Obstructive Pulmonary Disease (COPD) patients and associated to worse lung function. COPD is characterized by irreversible airflow obstruction, partly due to an increased cholinergic environment. Our goal was to investigate muscarinic signalling in COPD fibrocytes. Fibrocytes were isolated from 16 patients with COPD’s blood and presence of muscarinic M3 receptor was assessed at the transcriptional and protein levels. Calcium signalling and collagen gels contraction experiments were performed in presence of carbachol (cholinergic agonist) +/- tiotropium bromide (antimuscarinic). Expression of M3 receptor was confirmed by Western blot and flow cytometry in differentiated fibrocytes. Immunocytochemistry showed the presence of cytoplasmic and membrane-associated pools of M3. Stimulation with carbachol elicited an intracellular calcium response in 35.7% of fibrocytes. This response was significantly blunted by the presence of tiotropium bromide: 14.6% of responding cells (p<0.0001). Carbachol induced a significant contraction of fibrocytes embedded in collagen gels (13.6 ± 0.3% versus 2.5 ± 4.1%; p<0.0001), which was prevented by prior tiotropium bromide addition (4.1 ± 2.7% of gel contraction; p<0.0001). Finally, M3-expressing fibrocytes were also identified in situ in the peri-bronchial area of COPD patients’ lungs, and there was a tendency to an increased density compared to healthy patient’s lungs. In conclusion, around 1/3 of COPD patients’ fibrocytes express a functional muscarinic M3 receptor. Cholinergic-induced fibrocyte contraction might participate in airway diameter reduction and subsequent increase of airflow resistance in patients with COPD. The inhibition of these processes could participate to the beneficial effects of muscarinic antagonists for COPD treatment.